2017
DOI: 10.1016/j.nmd.2016.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Ephedrine treatment for autoimmune myasthenia gravis

Abstract: We studied the effect and safety of ephedrine as add-on treatment for patients with myasthenia gravis with acetylcholine receptor antibodies (AChR MG), who do not sufficiently respond to standard treatment. Four patients with AChR MG were included in a placebo-controlled, double-blind, and randomised, multiple crossover series of n-of-1 trials. Each n-of-1 trial consisted of 3 cycles, in which two 5-day intervention periods were followed by 2 days washout. In each cycle, ephedrine 50 mg daily in 2 doses was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 30 publications
0
31
0
Order By: Relevance
“…The clinical results of the trial have been reported elsewhere [29]. Briefly, four patients completed three treatment cycles each containing a treatment period with ephedrine and placebo in addition to their usual medications.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical results of the trial have been reported elsewhere [29]. Briefly, four patients completed three treatment cycles each containing a treatment period with ephedrine and placebo in addition to their usual medications.…”
Section: Resultsmentioning
confidence: 99%
“…Parts of Additional file 1 (the briefing document) have been published by AF Lipka et al in Neuromuscular Disorders [29]. Marcel Timmen, director of the Dutch association for neuromuscular disorders (Spierziekten Nederland), provided general support for this project.…”
Section: Acknowledgementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Drugs that activate β‐adrenergic receptors, including ephedrine and albuterol, offer a therapeutic benefit in certain forms of congenital MG . Ephedrine has also been used in autoimmune MG, and was recently successful in a small n ‐of‐1 trial . Ghazanfari et al .…”
Section: Treatment Of Musk Mg In Passive Transfer Modelsmentioning
confidence: 99%
“…In addition to the promotion of presynaptic vesicle recycling [98], the effects of BDNF in the synapse are regulated by way of Wnt canonical signaling pathway [99] and activated by β2-adrenoceptor agonists (via intracellular signaling pathways, perhaps including the cyclic adenosine monophosphate, cAMP/protein kinase A/cAMP-responsive element-binding protein pathway) to maintain the structural and functional integrity of motor endplates [100]. The therapeutic pre- and postsynaptic benefits of β-adrenoceptor agonists (salbutamol and ephedrine) have been reported in MuSK MG animal models [101], neonatal myasthenia gravis (FARIS, caused by fetal AChR γ-subunit antibodies [72,73]) [102] and MG patients with nAChR antibodies [103] as well as various types of congenital myasthenic syndrome [104,105] including the patients suffering from mutations in MuSK [106] and Lrp4 [107]. …”
Section: Agrin Cortaction and The Other Synapse-related Proteins mentioning
confidence: 99%